Rancang Bangun Pengendali Motor 1 Fasa Dengan Metode Zero Crossing Detector Berbasis Arduino - Sutriyono, Agus; , Aris Budiman, S.T., M.T (2017)
AC motor speed control system can be done with several methods, such as frequency adjustment, poles number changing, resistance adjustment, armature input voltage adjustment, vector controlling, grid voltage and frequency adjusment, and additional elecrtronic components usage. The 1-phase AC motor control system that used in this research uses phase angle counting (zero crossing detector) as reference and adjust triac triggering which will make the AC motor speed control system in easy way. The change of triac delay trigger will change the current and voltage output, so the power of the 1-phase AC motor will also change according to the triac trigger. With this zero crossing detector circuit as a device to detect the sinusoidal wave cross (zero point between positive and negative value) at AC voltage can be given a trigger refference signal to the triac gate. The motor speed adjustment system uses Arduino UNO R3 microcontroller and its software to show the duty cycle, delay and the zero crossing refference signal at the 2x16 LCD monitor. According to the conducted experiments, with 10 % increment, the duty cycles are is 10% until 100%. From that range, we get 30 volt until 200 volt of output voltage, and the current are 0,14 Ampere until 1,49 Ampere, but the current will drop to 0,71 Ampere when the duty cycle is 100% and the motor rotates at 183 rpm until 1509 rpm. This data shows that the device in this research can work to adjust the 1-phase AC motor speed.